Payout taxes and the allocation of investment - Becker, Bo; Jacob, Marcus; Jacob, Martin (Journal of Financial Economics, 2013)
When corporate payout is taxed, internal equity (retained earnings) is cheaper than external equity (share issues). If there are no perfect substitutes for equity finance, payout taxes may therefore have an effect on the investment of firms. High taxes will favor investment by firms who can finance internally. Using an international panel with many changes in payout taxes, we show that this prediction holds well. Payout taxes have a large impact on the dynamics of corporate investment and growth. Investment is “locked in” in profitable firms when payout is heavily taxed. Thus, apart from any level effects, payout taxes change the allocation of capital.